If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 8 + 3x = 19 Reorder the terms: 8 + 8x + 3x = 19 Combine like terms: 8x + 3x = 11x 8 + 11x = 19 Solving 8 + 11x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 11x = 19 + -8 Combine like terms: 8 + -8 = 0 0 + 11x = 19 + -8 11x = 19 + -8 Combine like terms: 19 + -8 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| 4senx*cosx+2senx-2cosx-1=0 | | 2x^2(7x-3)= | | 4+2(3)=6+2(2) | | 2x+8=-6x+15 | | (7x^2)(6x)= | | 6x-2(2x+8)=18 | | X*2+3x-4=0 | | 5x-4y=40slope | | -4(4+2x)-3=-51 | | 10x+24=2x-16 | | 8x^3-128x=0 | | 4x^2-74x+70= | | -3(-2-3v)+4v=58 | | 10x+24=x^2+16 | | 0=-0.04x^2+0.8x+3 | | 2(x+3)=18-2x | | 4x-(3x-5)=10x+8+6 | | 5(3y-8)=10y | | y^2=4FX | | .25s+10=.75s | | =-0.04x^2+0.8x+3 | | (2x+3y+4)dx+(3x+4y+5)dy=0 | | 4x+32=2(3x-1) | | x+(x+2)+(x+4)+(x+6)+(x+8)=455 | | 8w-12=4(w-6) | | 8b+3b=-1 | | 3ydx=(3x^2-1)(dx-dy) | | 2(3j-2)+6=4(1+j) | | 3c*-d= | | 7+30x=15+13 | | x^2+8x+64=48 | | y=-0.625+87 |